A framework to assess impacts of path dependence on urban planning outcomes, induced through the use of decision-support tools. (August 2021) - Schindler, Mirjam; Dionisio, Rita
Abstract: Urban planning stakeholders can use decision-support tools (DST) to foster transformation towards sustainable urban morphologies. This paper proposes an analytical framework to support urban planning practitioners in assessing how the use of DST might impact planning outcomes due to path dependence. We identify five key dimensions of path dependence in a spatial socio-technical system as analytical framework to assess the influence of DST on planning outcomes. Potential impacts on urban planning outcomes are analysed by applying the proposed framework to a particular spatial socio-technical system, namely New Zealand's use of DST to support urban planning decision-making towards sustainable urban morphologies. The assessment framework and comparative case study analysis illustrate how the interaction between planning culture and some DST features can influence decisions pertaining to urban morphologies and raise awareness about DST-induced path dependence. Highlights: How can decision-support tool (DST) use impact urban outcomes due to path dependence? An analytical framework to assess potential path dependence through DST use Case study application of this framework to a spatial socio-technical system Call for critical evaluation of practices related to choices and use of DST Urban transformation requires awareness and mitigation of path dependence.